Kinematics of the Cabot Fault Zone: An example of long-lived large-scale orogen-parallel transcurrent movements during the accretionary history of the northern Appalachian orogen, Canada - Brem, Arjan; Lin, Shoufa; van Staal, Cees (Atlantic Geoscience, 2026)
The Cabot Fault Zone (CFZ) in the western Newfoundland Appalachian orogen is a long-lived crustal-scale tectonic zone that separates the Corner Brook Lake block (CBLB) of the internal Humber Zone from the Dashwoods block of the western Dunnage Zone. The two blocks comprise different tectonostratigraphic assemblages and had distinct Early Palaeozoic tectonic histories. Using field and microscopic observations, five phases of deformation have been recognized in the CFZ, demonstrating a progressive evolution of the tectonic zone from mid-crustal levels (D1 gneisses and D2 mylonites) to shallow-crustal levels (D5 cataclasites). Integrating available geochronological data, the CFZ has recorded a protracted history of dominant oblique-dextral transcurrent movement, as evidenced by well-developed Late Ordovician–earliest Silurian (post-Taconic) D1 and late Early Silurian to Early Devonian (post-Salinic) D2 fabrics. Large-scale (i.e., 100s of km) of Early Palaeozoic orogen-parallel movement along the CFZ can explain the present-day juxtaposition of the distinct CBLB and the Dashwoods block. Such large-scale orogen-parallel motion implies that presently neighbouring terranes could have been far apart during convergence and ocean closures, which has significant implications for tectonic interpretation of the Early Palaeozoic evolution of the Newfoundland Appalachian orogen.